Detection of Antimicrobial Activities and Bacteriocin Encoding Genes in Lactic Acid Bacteria Isolated from Fermented Foods in Kirtipur - Gurung, Sandhya; Sharma, Supriya; Adhikari, Sanjib; Rijal, Komal; Poudel, Pramod; Panta, Om Prakash; Ghimire, Prakash (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The objective of this study was to isolate and identify Lactic Acid Bacteria (LAB) from fermented foods and evaluate their antimicrobial activities as well as to detect bacteriocin encoding gene and also determine probiotic effect of selective LAB isolates. Methods: A total of 26 fermented food samples were collected from different small scale dairy shops and community of Kirtipur, Kathmandu and LAB were isolated following standard plate count method. Preliminary identification of isolates was done by staining and biochemical tests. The gene encoding specific bacteriocin were detected using polymerase chain reaction. Results: Based on the morphological, microscopy and biochemical characteristics, a total of 40 LAB were screened; among them 25 (62.5%) were Gram-positive rod shape LAB A (Lactobacillus spp) type and 15 (37.5%) isolates were gram-positive cocci shape LAB B type. Among 40 isolates of Lactic Acid Bacteria, cell free supernatant of 24 (60%) showed antibacterial activity with highest being that of isolates Ca3 and Ca4 LAB against all 6 test bacteria. Isolated LAB were most effective against Pseudomonas aeruginosa i.e. out of 24 LAB 20 (83.33%) isolates showed inhibition zone. Enterocin gene were detected in 4 (16.66%) LAB isolates while nisin and pediocin gene were not detected in isolated LAB. All 9 selected LAB isolates were able to resist high acidic condition at pH 3 till 24 hrs, 0.5% and 1% bile salt concentration while isolates C3 (Enterococcus spp) and Ca3 (Lactobacillus spp) were able to resist pH 3 till 48 hof incubation. Therefore, they can survive in stomach high acidic and bile condition indicating their probiotic potentiality. Conclusion: These findings emphasize LAB's potential as natural antibacterial agents that could be exploited in food preservation and as probiotics to improve human health.